THE PHENOMEN DIGNITARY OF THE NATION IAKOV MAKOGІN - Henyk, S. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Galichanin from Lviv region in the search of better fate it turns out abroad ocean gets american citizenship and passes military units elite units american army. To meate with pure american girl Syusann wihich fall in love handsome, healthy, clever and well-bread Ukrainian boy. Girl is the only one daughter one the richest one of the most rich american. Demobilization after 15 years service in the marine corps – there lound wedding. Get’s direct ucces to father’s money, new part of family throught many years uses then not for future enrichment or comfort but for solution of the older "Ukrainian question" in the most dramatic period stays Ukrainian AVG consisting of Soviet imperia. That which is done abroad to the call of the heart this ukrainian boy can outmatch a work complex embassy a big country.